2022
DOI: 10.3389/fnins.2022.1028776
|View full text |Cite
|
Sign up to set email alerts
|

Triple network activation causes tinnitus in patients with sudden sensorineural hearing loss: A model-based volume-entropy analysis

Abstract: Tinnitus can be defined as the conscious perception of phantom sounds in the absence of corresponding external auditory signals. Tinnitus can develop in the setting of sudden sensorineural hearing loss (SSNHL), but the underlying mechanism is largely unknown. Using electroencephalography, we investigated differences in afferent node capacity between 15 SSNHL patients without tinnitus (NT) and 30 SSNHL patients with tinnitus (T). Where the T group showed increased afferent node capacity in regions constituting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…The involvement of the insula and the rostral anterior cingulate cortex highlights their significance in the salience network or ventral attention network, crucial for detecting and filtering salient external stimuli and internal events, thereby facilitating the transition between activated networks such as the default mode network and the central executive or frontoparietal network. The superior frontal gyrus and the frontal pole, implicated in executive function and attentional control, are key components of the frontoparietal network, underscoring their role in directing attention and managing cognitive resources, which could be particularly relevant in modulating attention towards or away from tinnitus sounds [90]. Additionally, the involvement of sensory integration and executive regions suggests a complex interplay between auditory processing and higher-order cognitive functions, emphasizing the multisensory and multidimensional nature of tinnitus perception within these overarching neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the insula and the rostral anterior cingulate cortex highlights their significance in the salience network or ventral attention network, crucial for detecting and filtering salient external stimuli and internal events, thereby facilitating the transition between activated networks such as the default mode network and the central executive or frontoparietal network. The superior frontal gyrus and the frontal pole, implicated in executive function and attentional control, are key components of the frontoparietal network, underscoring their role in directing attention and managing cognitive resources, which could be particularly relevant in modulating attention towards or away from tinnitus sounds [90]. Additionally, the involvement of sensory integration and executive regions suggests a complex interplay between auditory processing and higher-order cognitive functions, emphasizing the multisensory and multidimensional nature of tinnitus perception within these overarching neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with obesity have reduced total brain and gray matter volume, which is attributed to neuroinflammation. Furthermore, the fronto-temporal regions, which are involved in the noise cancellation pathway, are also associated with obesity 3 , 22 , 23 . Since tinnitus is linked to the noise cancellation pathway 3 , these structural changes in the brain may contribute to the onset and persistence of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fronto-temporal regions, which are involved in the noise cancellation pathway, are also associated with obesity 3 , 22 , 23 . Since tinnitus is linked to the noise cancellation pathway 3 , these structural changes in the brain may contribute to the onset and persistence of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Previous studies of the causes of tinnitus, especially in neuroscience, have revealed possible mechanisms for tinnitus. 1 7 8 9 10 However, these mechanisms are still not sufficient to comprehensively define tinnitus owing to its highly heterogenous physiopathology.…”
Section: Introductionmentioning
confidence: 99%